Influence of type-4 dipeptidyl peptidase inhibition on endothelium-dependent relaxation of aortae from a db/db mouse model of type 2 diabetes: a comparison with the effect of glimepiride - Woodman OL (Dove Medical Press, 2019)
Owen L Woodman,1 Jacinta M Ortega,1 Joanne L Hart,1 Thomas Klein,2 Simon Potocnik11School of Health and Biomedical Sciences, RMIT University, Bundoora, VIC, Australia; 2Department of Cardiometabolic Diseases Research, Boehringer Ingelheim Pharma, Biberach, GermanyCorrespondence: Owen L WoodmanBaker Heart & Diabetes Institute, PO Box 6492, Melbourne 3004, AustraliaTel +61 38 532 1917Email owen.woodman@baker.edu.auPurpose: The aim of this study was to investigate the effects of the type-4 dipeptidyl peptidase (DPP-4) inhibitors linagliptin and vildagliptin as well as the sulfonylurea glimepiride on endothelium-dependent relaxation of aortae from female db/db mice with established hyperglycemia to determine whether these treatments were able to attenuate diabetes-induced endothelial dysfunction.Materials and methods: The mice were treated with glimepiride (2 mg/kg po per day, weeks 1–6, n=12), glimepiride plus vildagliptin (glimepiride 2 mg/kg po per day, weeks 1–6; vildagliptin 3 mg/kg po per day, weeks 4–6, n=11), glimepiride plus linagliptin (glimepiride 2 mg/kg po per day, weeks 1–6; linagliptin 3 mg/kg po per day, weeks 4–6, n=11) or linagliptin (3 mg/kg po per day, weeks 1–6, n=12). Endothelium-dependent relaxation using acetylcholine was assessed in the absence and presence of pharmacological tools (TRAM-34 1 μM; apamin 1 μM; N-nitro-L-arginine [L-NNA] 100 μM; 1H-[1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one [ODQ] 10 μM) to distinguish relaxation mediated by nitric oxide (NO).Results: Linagliptin was associated with a significant improvement in endothelium-dependent relaxation (ACh Rmax; db/db 41±1%, linagliptin 73±6%, p<0.05). The enhanced response was maintained in the presence of TRAM-34+ apamin (ACh Rmax; db/db 23±6%, linagliptin 60±6%, p<0.01), ie, when the endothelium-dependent relaxation was mediated by NO. There was no evidence for a contribution from KCa channel opening to responses under any conditions. Glimepiride had no effect on endothelium-dependent relaxation when given alone (ACh Rmax 38±3%). The addition of linagliptin or vildagliptin to glimepiride did not significantly improve endothelium-dependent relaxation. All treatments caused some decrease in aortic superoxide production but the effect of linagliptin was significantly greater than glimepiride (linagliptin 534±60 relative luminescence unit [RLU], glimepiride 1471±265 RLU, p<0.05).Conclusion: Linagliptin is superior to glimepiride in regard to the preservation of endothelium-dependent relaxation in the presence of hyperglycemia and the improvement in endothelial function in response to linagliptin treatment is associated with greater antioxidant activity compared to glimepiride.Keywords: diabetes, DPP-4 inhibitor, endothelium-dependent relaxation, glimepiride, linagliptin, reactive oxygen species